1991
DOI: 10.1007/bf02663751
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and identification of antioxidants in oats

Abstract: in Oats 365Eight separate solvent systems were used with groats and hulls of several lines of oats to determine which system resulted in the most effective, rapid extraction of antioxidants. Antioxidant activity at room temperature was estimated by using thin-layer chromatography (TLC) along with a f~-carotene spray. The greatest antioxidant activities were obtained with methanolic antioxidant extracts derived from Noble and Ogle oats and hulls. These extracts were added to soybean oil (SBO) and their effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
2
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 18 publications
4
53
2
2
Order By: Relevance
“…Subsequently, 10 fractions were isolated using reverse-phase HPLC and their structures were determined using gas chromatography-mass spectrometry. Cycloartenyl ferulate, 24-methylenecycloartanyl ferulate and campesteryl ferulate were identified as the major components of γ-oryzanol [40][41][42].…”
Section: Extraction Isolation and Identification Of The Active Compomentioning
confidence: 99%
“…Subsequently, 10 fractions were isolated using reverse-phase HPLC and their structures were determined using gas chromatography-mass spectrometry. Cycloartenyl ferulate, 24-methylenecycloartanyl ferulate and campesteryl ferulate were identified as the major components of γ-oryzanol [40][41][42].…”
Section: Extraction Isolation and Identification Of The Active Compomentioning
confidence: 99%
“…Seguiramse os procedimentos descritos por Duve;White (1991), adaptado por Filho (2003). Os reveladores utilizados para avaliar a presença de compostos com atividade antioxidante foram: 9 mg de β-caroteno em 30 mL de clorofórmio (CHCl 3 ) + 20 mg de ácido linoléico (C 18 H 32 O 2 ) em 60 mL etanol (C 2 H 6 0).…”
Section: Fenólicos Totaisunclassified
“…During selection of soybeans for a particular food application or a particular seed breeding program, it is important to know the major factors affecting soybean quality such as protein and oil contents, the chemical components of protein and oil, and seed appearance (Liu ef a/., 1995). Also, there has been an increasing concern about the study of the sterol fraction from seed oils because a specific sterol found in oats, A^-avenasterol, was effective in retarding soybean oil deterioration (Duve and White, 1991).…”
Section: Introductionmentioning
confidence: 99%